Glycoprotein 96 in Peritoneal Dialysis Effluent-Derived Extracellular Vesicles: A Tool for Evaluating Peritoneal Transport Properties and Inflammatory Status - Fang, Junyan; Tong, Yan; Ji, Ouyang; Wei, Shan; Chen, Zhihao; Song, Ahui; Li, Pu; Zhang, Yi; Zhang, Huiping; Ruan, Hongqiang; Ding, Feng; Liu, Yingli (Frontiers in Immunology, 2022)
Background Extracellular vesicles (EVs) from peritoneal dialysis effluent (PDE), containing molecules such as proteins and microRNAs (miRNAs), may be potential biological markers to monitor peritoneal function or injury. Peritoneal inflammation is an important determinant of peritoneal solute transport rate (PSTR). Thus, the aim of this study is to determine whether the specific proteins capable of evaluating the PSTR could be found in PDE-EVs, and explore the underlying mechanism for the association between PSTR and peritoneal inflammation. Methods Sixty patients undergoing peritoneal dialysis (PD) were divided into two groups: high/high average transport (H/A) group (PET >0.65) and low/low average transport (L/A) group (PET <0.65). EVs derived from PDE (PDE-EVs) were isolated by ultracentrifugation. Proteomic analysis was performed to explore the differentially expressed proteins and identify the potential biomarkers in PDE-EVs from the two groups, and we focused on glycoprotein 96 (GP96) as it could be involved in the inflammatory process. The expression of GP96 in PDE-EVs and inflammatory cytokines was quantified by real-time PCR and enzyme-linked immunosorbent assay. The infiltration of macrophages and neutrophils into the peritoneum was detected using immunohistochemistry in a PD rat model. Results The expression of PDE-EVs-GP96 was significantly higher in the H/A group, and was positively correlated with the PSTR and the level of the inflammatory factor interleukin (IL)-6. GP96-enriched EVs enhanced the secretion of proinflammatory cytokines IL-1β, IL-6, tumor necrosis factor (TNF)-α, and IL-8 in macrophages, which was reversed by a pharmacological GP96-specific inhibitor (PU-WS13). The GP96 inhibitor also reduced local peritoneal inflammation by decreasing the infiltration of inflammatory cells and levels of proinflammatory cytokines (IL-6 and TNF-α) and chemokines (CCL2, CXCL1, and CXCL2) in a PD rat model. Conclusions PDE-EVs-GP96 is a new promising tool to evaluate the status of peritoneal inflammation and PSTR, and the mechanism may be related to affecting the inflammatory properties of macrophages.